Treatment of interstitial cystitis in women - Ching-Hung Hsieh; Wei-Chun Chang; Ming-Chao Huang; Tsung-Hsien Su; Yiu-Tai Li; Han-Sun Chiang (Elsevier, 2012)
Interstitial cystitis (IC) has been described as a chronic debilitating sterile inflammatory multifactorial bladder syndrome of unknown etiology. IC is characterized by bladder pain (or suprapubic pain) associated with urgency, urinary frequency, and nocturia. Because the pathogenesis of IC remains unclear, it is still an enigma and represents a diagnostic and therapeutic challenge. The diagnosis of IC remains unclear and is based on exclusion of other diseases. Consequently, IC has usually been underdiagnosed, and the consensus on best available treatment for the disease is lacking. The current goal for the treatment of IC is usually symptomatic relief, and treatment protocols are based on empiricism. Multiple forms of therapy are available, and most patients can be managed conservatively. Nevertheless, the efficacy of most treatments is short term. This review article gives an overview of the available treatments for IC.